Atypical Presentation of Acute Appendicitis: A 32-year-old Man with Gastroenteritis Symptoms; an Educational Case - Seyedhosseini-Davarani, Seyedhossein (Adv J Emerg Med, 2017)
INTRODUCTION: Appendicitis is a common condition that almost always requires emergency surgery. The diagnosis is clear when the patient presents with classic symptoms. However, presentation may be variable due to variations in the position and length of the appendix. CASE PRESENTATION: Here, we report a 32-year-old man who presented with diarrhea and lower abdominal pain. Physical examination revealed a generalized abdominal tenderness, more prominent in the lower abdomen, including the right and left quadrants. Abdominal ultrasound failed to show any findings supportive of the diagnosis of appendicitis. Further investigation with abdominopelvic computed tomography (CT) with intravenous and oral contrast revealed retrocecal appendicitis. The patient was discharged home after a non-complicated appendectomy. CONCLUSION: Emergency physicians should be aware that appendicitis may not always show up with a typical presentation and they should consider the possibility of appendicitis when evaluating an acute abdomen to prevent any delay in diagnosis of atypical presentations.